Способ экспресс-индикации связности дисперсных материалов - Василевский М. В. Михаил Викторович; Некрасова К. В. Ксения Викторовна; Разва А. С. Александр Сергеевич; Зыков Е. Г. Евгений Геннадьевич
опубл. 20.06.10